Study of Graphite Cycling in Sulfide Solid Electrolytes. Issue 11 (31st July 2020) - Höltschi, Laura; Jud, Franziska; Borca, Camelia; Huthwelker, Thomas; Villevieille, Claire; Pelé, Vincent; Jordy, Christian; El Kazzi, Mario; Novák, Petr
Abstract : We report the excellent cycling stability of graphite in combination with two types of sulfide solid electrolytes, 0.75Li2 S-0.25P2 S5 (LPS) and 0.3LiI-0.7(0.75Li2 S-0.25P2 S5 ), and discuss the stability of the graphite-solid electrolyte interface by analyzing the normalized cumulative irreversible charge and the total amount of lithium consumed at the lithiated state. The rate limitations and the influence of the morphology and the size of graphite particles on the utilization of the electrode are studied as well. At higher current densities, the utilization of the graphite is decreasing as a consequence of the poor effective ionic conductivity of the composite electrode, which is also evidenced by the increasing polarization and ohmic resistance across the electrode.